The Role of Narcism in The Detection of Financial Fraud: A Systematic Literature Review - Amalia, Dewi; Tarjo, Tarjo; Muhammad, Erfan; Said, Jamaliah (AKRUAL: JURNAL AKUNTANSI, 2023)
Introduction / Main Objectives: This article aims to map the literature review regarding financial fraud detection by analyzing narcissistic individuals when using social media. Background Problems: The writer found indications of narcissism in the literature with the keywords "the impact of narcissism using social media" and "detection of financial fraud on narcissistic behavior." The findings show that narcissism is a personality disorder characterized by excessive self-assessment, thirst for recognition, and lack of empathy. Narcissism can negatively influence individuals when uploading content on their social media. The rise of wealth-flexing content is evidence of selfish individuals trying to gain social recognition. Without realizing it, flexing range triggers destructive perceptions from other people, especially if they excessively highlight wealth items on virtual networks. Perceptions about alleged unethical behavior in financial crimes. Even though it does not have a strong correlation, these allegations of narcissistic individuals can have the potential to commit financial fraud. Novelty: The novelty of this research is how to map the literature review regarding narcissism in detecting financial fraud Research Method: This article uses the bibliometric method to describe research developments related to narcissism and financial fraud. Findings/Result: The findings presented results from an empirical review of 207 Scopus-indexed papers. The mapping results show that 40 pieces meet the criteria for an empirical study of narcissism. Conclusion: Through this bibliometric approach, the authors conclude that although there is no strong correlation, narcissistic individuals can potentially commit financial fraud.